Assessment of spatial mobility among young men who have sex with men within and across high HIV prevalence neighborhoods in New York city: The P18 neighborhood study. (November 2020) - Duncan, Dustin T.; Regan, Seann D.; Park, Su Hyun; Goedel, William C.; Kim, Byoungjun; Barton, Staci C.; Halkitis, Perry N.; Chaix, Basile
Highlights: Most studies investigating the role of neighborhoods in HIV-related outcomes among men who have sex with men (MSM) exclusively focus on the residential environment. Spatial mobility was documented with both self-reported survey data and objective GPS data, which provided uncorrelated information. Almost two-thirds (62.9%) of participants' GPS points were recorded in NYC ZIP code tabulation areas within the highest quartile of HIV prevalence. Compared to males, it was found that transfemale, genderqueer, and other MSM spent a much higher fraction of their non-home GPS time in high HIV prevalence areas. Abstract: The purpose of this study was to examine and quantify spatial mobility among HIV-negative young men who have sex with men (YMSM) within and across high prevalence HIV neighborhoods in New York City (NYC). We completed an analysis with global positioning system (GPS) and survey data to quantify spatial mobility for participants enrolled in the P18 Neighborhood Study (analytic n = 211; 83.4%). Spatial mobility was documented with self-reported survey data and objective GPS data, which was uncorrelated. Nearly one-quarter of participants (26.1%) said that they consider the neighborhood in which they currently live to differ from the neighborhood in which they had sex most frequently. In addition, 62.9% of participants' GPS points were recorded in NYC ZIP Code Tabulation Areas within the highest quartile of HIV prevalence. Future studies of YMSM populations should be conducted to examine how environments beyond the residential neighborhood can influence sexual health, which may guide HIV prevention services.